Estimation of Levelized Cost of Energy for Small Modular Reactors in Colombia: A Monte Carlo Simulation Approach - Camilo, Prieto; Diego, Patiño; José, Vuelvas (International Journal of Energy Economics and Policy, 2025)
Small modular reactors (SMRs) offer significant prospects for Colombia to diversify and decarbonize its energy mix by 2038, as specified in the National Energy Plan (PEN) 2022-2052. However, current assessments primarily focus on capital expenditure (CAPEX) indicators, such as the overnight capital cost (OCC), while overlooking the Levelized cost of energy (LCOE), which provides a more comprehensive measure of long-term economic viability. This study employs a Monte Carlo simulation to calculate the LCOE of a 300 MW SMRs in Colombia for the 2038-2042 period, including probabilistic distributions for OCC, operational expenditures (OPEX), fuel cost, and capacity factor. The results indicate a median LCOE of $77.71/MWh, with a range from $68.26/MWh in optimistic scenarios to $117.80/MWh in pessimistic ones. These findings suggest that SMRs could serve as a cost-competitive alternative to coal-fired power plants, particularly when externalities such as carbon emissions are considered. Sensitivity analysis identifies OCC and the weighted average cost of capital (WACC) as the most influential cost drivers. Additionally, fuel procurement strategies, including reprocessed fuel and long-term contracts, can further reduce operational costs. This study underscores the importance of integrating LCOE into energy planning and calls for regulatory and financial mechanisms to support SMRs deployment in Colombia.